Exposure to PAHs and health risk assessment in three sewage irrigations - Jinsheng Zhao; Minghua Zhou; Na Zhang (Universiti Kebangsaan Malaysia, 2016)
The sewage irrigation area in Tianjin reached 6 billion m2 in 2003 which accounts for 22% of the irrigated areas. Polycyclic aromatic hydrocarbons (PAHs) contamination caused by sewage irrigation on agricultural land has attracted considerable attention because of their toxic and hazardous risks to human beings. In order to evaluate the health risk of PAHs to farmers in four age groups, a multimedia/multipathway exposure model was applied. The results showed that the chronic daily intake (CDI) of children, adolescents, adults and the aged to the 16 PAH compounds exposure were 2.83, 2.34, 1.44, 1.05 μg·kg-1·d-1, respectively. The non-cancer risk of life long exposure in sewage irrigation was 2.75×10-3 and the cancer risk was 2.49×10-5. From the long-term safety point of view, the health risks caused by PAHs were at a relatively high level. Hence, we suggest that crops of sewage irrigated areas and their distribution channels should be re-concerned by the government in the future city planning.